Nematodes from the Gulf of California. Part 1. The genera Ceramonema Cobb, 1920, Pselionema Cobb in Cobb, 1933 and Pterygonema Gerlach, 1954 (Nematoda: Ceramonematidae) - Holovachov, O.; De Ley, P.; Baldwin, J.; Rocha-Olivares, A.; Tandingan De Ley, I.; Mundo-Ocampo, M. (Nematology, 2008)
The morphology and morphometry of nematodes of six species of the family Ceramonematidae is described using light and scanning electron microscopy. In this paper, we describe two new species and redescribe two known species of Ceramonema and one new species each of Pselionema and Pterygonema. Ceramonema altogolfi sp. n. is characterised by the 0.8-1.3 mm long body, 187-247 body annules, weakly developed zygapophyses, presence of intracuticular vacuoles, sexual dimorphism in amphid shape, presence of vaginal sclerotisation, complex gubernaculum and relatively uniform anal and cloacal annules, whilst C. inguinispina sp. n. has a 0.8- 1.1 mm long body, 135-191 body annules, weakly developed zygapophyses, presence of intracuticular vacuoles, sexual dimorphism in amphid shape, absence of vaginal sclerotisation, thorn-shaped precloacal projection, plate-like gubernaculum and double cloacal annule. Pselionema psednum sp. n. is distinguished by 1.4-1.7 mm long body, 251-292 body annules, weakly developed zygapophyses, absence of intracuticular vacuoles, sexual dimorphism in amphid shape and Pterygonema mexicanum sp. n. is characterised by having amphids lacking a central thorn-like projection and pharynx with a distinct posterior glandular bulb. Populations of Ceramonema rectum and Ceramonema cf. yunfengi are also described. The male cloacal region of the species examined appears to be a rich potential source of taxonomic characters that have as yet received insufficient attention for this family. Keywords – Baja California, Ceramonema altogolfi sp. n., Ceramonema inguinispina
NeMys doc_id: 17875